Integrasi Teknologi Artificial Intelligence dalam Pengolahan Gambar dan Produksi Video - Irsyada, Abdulloh Eizzi; Setyorini, Setyorini; Arifin, Jaenal; Andini, Titania Dwi; Indahsari, Rina Dewi (Pakis Journal Institute, 2026)
Artificial Intelligence is now an integral part of learning activities, especially for the younger generation. This includes digital image processing and video production. These activities are driven by the importance of mastering digital technology as one of the key competencies in facing the era of Industry 4.0 and Society 5.0, particularly for vocational high school students who are being prepared for careers in the digital creative field. The implementation methods include interactive training, hands-on practice with AI-based software, and guidance in digital content creation projects. Students are introduced to various AI applications and tools for automatic image editing, background removal, resolution enhancement, and the creation of text- and synthetic voice-based videos. The results of these activities demonstrate an improvement in students' understanding and skills in utilizing AI technology to support their creative processes. The digital products created through the training also demonstrate improved visual quality and efficiency in the production process. This activity is expected to serve as a model for integrating AI technology into vocational curricula and to foster the emergence of a creative generation adaptable to technological advancements.